Thyrotrophic status in patients with pituitary stalk interruption syndrome. Issue 2 (January 2018) - Zhang, Qian; Zang, Li; Li, Yi-Jun; Han, Bai-Yu; Gu, Wei-Jun; Yan, Wen-Hua; Jin, Nan; Chen, Kang; Du, Jin; Wang, Xian-Ling; Guo, Qing-Hua; Yang, Guo-Qing; et al.
Abstract : Abstract: Pituitary stalk interruption syndrome (PSIS) is associated with simultaneous or subsequent pituitary hormone deficiencies (PHDs). Although the clinical features of multiple PHDs are well known, the status of the thyrotrophic axis in PSIS has not been thoroughly investigated. The clinical data of 89 PSIS patients and 34 Sheehan syndrome (SS) patients were retrospectively analyzed. The prevalence of central hypothyroidism in the PSIS patients and the SS patients was 79.8% and 70.6%, respectively. The thyroid-stimulating hormone (TSH) levels in the PSIS patients were significantly higher in comparison with the SS patients (5.13 ± 3.40 vs 1.67 ± 1.20 mU/L, P  < .05). TSH elevation (8.79 ± 3.17 mU/L) was noticed in 29 of 71 (40.85%) hypothyroid PSIS patients but not in the 24 hypothyroid SS patients. The TSH levels in the hypothyroid PSIS patients were significantly higher in comparison with the euthyroid PSIS patients (5.42 ± 3.67 vs 3.66 ± 1.50 mU/L). Thyroid hormone replacement significantly reduced the TSH levels in the PSIS patients with elevated TSH levels from 7.24 ± 0.98 to 1.67 ± 1.51 mU/L ( P  < .05). The logistic regression analysis suggested that TSH level was not significantly associated with pituitary stalk status and height of the anterior pituitary gland. PSIS is a newly recognized cause of central hypothyroidism. The proportion and amplitude of TSH elevations are higher in PSIS than in other causes of central hypothyroidism.